Pengembangan Sistem Akuisisi Data Nirkabel untuk Pengukuran Distribusi Suhu Bawah Permukaan - Rahman Arifuddin; Didik R. Santoso; Onny Setyawati (Fakultas Teknik, Universitas Brawijaya, 2015)
Subsurface temperature distribution measurement can be performed using non-contact methods such as remote sensing and other satellite imagery, and method of contact is by direct measurement at the observation area. In this research a contact method was used by injecting iron pipes equipped with sensor into the ground. The digital temperature sensor that can reduce noise, communication systems using wireless networks, and data processing system user interface were used. Result of measurement and processing of the data showed that the distribution of heat towards one of the slave due to the sunlight direct exposure was 31oC in areas without anomalies